Soluble urokinase-type plasminogen activator receptor predicts peripheral artery disease severity and outcomes. (February 2021) - Höbaus, Clemens; Ursli, Martin; Yussef, Sarah Mohammed; Wrba, Thomas; Koppensteiner, Renate; Schernthaner, Gerit-Holger
Soluble urokinase-type plasminogen activator receptor (suPAR) is associated with chronic kidney disease (CKD) severity and peripheral artery disease (PAD). We hypothesize an association of PAD severity and suPAR in patients without advanced CKD and further risk stratification according to the Kidney Disease: Improving Global Outcomes (KDIGO) guidelines. For study purposes, suPAR was measured in 334 PAD patients (34% women, age 69 (62–78) years, eGFR 68 ± 20 mL/min/1.72 m 2 ) by commercial ELISA. Patients were followed for 10 years to assess long-term all-cause survival by Cox regression. Higher suPAR levels were associated with lower ankle–brachial index ( R = −0.215, p = 0.001) in patients with PAD without media-sclerosis ( n = 236). suPAR levels inversely correlated with decreased glomerular filtration rate ( R = −0.476, p < 0.001) and directly correlated with urinary albumin-to-creatinine ratio ( R = 0.207, p < 0.001). Furthermore, higher suPAR levels associated with a higher KDIGO risk score ( p < 0.001). Baseline suPAR was significantly associated with all-cause mortality (HR 1.40 (95% CI 1.16–1.68), p < 0.001) over 10 years. suPAR remained associated with mortality (HR 1.29 (1.03–1.61), p = 0.026) after multivariable adjustment for age, sex, cardiovascular risk factors, and eGFR. Future research may define a standard role for suPAR assessment in PAD's work-up and treatment, especially in patients with CKD.